Development of the SWARA (Stimulus, Wondering, Active, Reflective, and Applicative) Music Learning Model in Elementary Education: A Systematic Literature Review - Desyandri Desyandri; Indra Yeni; Mansurdin Mansurdin; Hana Shilfia Iraqi; Raudhotul Jannah (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2025)
This study aims to develop a conceptual music learning model named SWARA (Stimulus, Wondering, Active, Reflective, and Applicative) based on deep learning principles and local cultural values through a systematic literature review (SLR). The review followed the PRISMA 2020 protocol by analyzing peer-reviewed articles indexed in Scopus and SINTA databases published between 2020 and 2025. Forty-eight relevant studies were selected through rigorous inclusion and exclusion criteria and further appraised using the Joanna Briggs Institute (JBI) critical appraisal tool. Thematic analysis revealed four dominant themes: (1) the role of deep learning in music education, (2) the integration of local cultural values, (3) project-based and collaborative music learning, and (4) the use of digital technology to enhance musical experiences. Based on these findings, the SWARA model is proposed as an innovative learning framework that integrates deep inquiry, local cultural values, collaborative creation, and digital augmentation. The model is expected to support meaningful, reflective, and culturally responsive music learning in elementary education. This study contributes theoretically to the development of contemporary music pedagogy and practically by offering a structured model for deep learning-oriented music instruction.